Extremism Concerns Growing in West and Predominantly Muslim Countries : Worries Especially Widespread in Western Europe and U.S. - Poushter, Jacob; Pew Research Center (Pew Research Center, 2015)
This report analyzes concern about Islamic extremism among publics in 21 countries. It is based on 21,235 face-to-face and telephone interviews with adults 18 and older conducted from April 5 to May 21, 2015.
Keywords: Islamismo; Terrorismo -- Encuestas -- Movimientos extremistas